The longer-term effects of IVF on offspring from childhood to adolescence - Hart, R. J.; Wijs, L. A. (Frontiers in Reproductive Health, 2022)
It is well established that there are increased pregnancy related complications for a woman who conceived through ART (assisted reproductive treatment). Further, it is known that the risk to the child born is greater, related to prematurity and a greater risk of growth restriction, and a greater risk of congenital malformations, although some of these risks may relate to underlying infertility, rather than the ART treatment per se. Consequently, it may be expected that there is a greater risk to the longer-term health of the child who is born form ART. However, in contrast it appears the evidence about long-term health of children conceived through ART is reassuring. Although, it is recognised that many of the studies in this field come with limitations. Low participation numbers are one of the major limitations, making subgroup analyses for different types of ART or different types of infertility difficult, and studies are often limited by short follow-up periods. Additionally, the rapid changes over time in ART, limit the generalisability and significance of long-term findings. Well-designed studies investigating the long-term health outcomes of ART-conceived offspring, as well as research investigating different aspects of the ART procedure are imperative. Although, conclusions form childhood hospitalisation data from the UK, the long-term follow-up and quality of life study from researchers in Melbourne and data published from the Western Australian Growing Up Healthy Study will go a long way to help reassure current and prospective parents who may ultimately require ART to conceive.